BOLSA FAMÍLIA PROGRAM : A Static Overview of Educational Conditions in the Municipality of Paulistas/MG (REMUNOM, 2024)
The present study aims to discuss the influences of the ‘Bolsa Família Program’ on income transfer for families in situations of financial and social vulnerability in the city of Paulistas, located in the interior of Minas Gerais. Income transfer is intended to promote access to public policies. This study seeks to explore, based on data provided by the municipality, how the Bolsa Família Program (PBF) impacts educational dynamics. A qualitative approach was chosen to investigate the educational conditions associated with PBF and its effects on school attendance in the municipality.